Acto abstracto de enajenación inscripción y fe pública en Derecho Alemán. Nociones sumarias. - Dassen, Julio (Lecciones y Ensayos, 2025)
Acto abstracto de enajenación inscripción y fe pública en Derecho Alemán. Nociones sumarias.